Health Promotion on PHBS: Efforts to Change Household Strata in X District Central Java - Rahayuni, Riyana; Raharjo, Bambang Budi; Widowati, Evi (Jurnal Kesehatan Vokasional, 2025)
Background: Clean and Healthy Living Behavior (PHBS) serves as a key indicator for improving community health status in alignment with the 2015–2030 Sustainable Development Goals (SDGs), particularly in promoting healthy lives and well-being for all segments of society.Objective: This research aimed to determine the differences in the PHBS strata of households in Pati Regency before and after health promotion interventions.Methods: This study employed a quasi-experimental design (pre-experimental design) with a pretest–posttest control group model. Sampling used purposive sampling, comprising 32 control group participants (Trangkil and Margoyoso Districts) and 32 experimental group participants (Margorejo and Wedarijaksa Districts).Results: The control group showed no improvement in PHBS strata before and after the observation period (p = 1.000 > 0.05), while the experimental group demonstrated a significant increase following the video-based health promotion intervention (p = 0.000 < 0.05).Conclusion: Health promotion delivered through drama-based educational video media is effective in improving household PHBS strata, particularly shifting households from the Madya to the Utama stratum.